Performando la patria: "Los patriotas de Lima en la noche feliz" - Santistevan, Alfonso (2022)
Los patriotas de Lima en la noche feliz, a stage play that is part of the performative program of the declaration of the independence of Peru in 1821, has been mostly studied based on its content and style. This article reviews the way this play has been approached from different disciplines and proposes a study from the aesthetics of the performative. From an analysis of the performative components, both mimetic and ritual, it is suggested to pay attention to the exclusions, the symbolic and fictional spaces, and the character hierarchy that the play proposes. In this way, this study reveals the play’s contradictions and limitations when it comes to representing the emerging Peruvian republic: the inaugural work of republican theater envisions a rational, “civic” and white/creole Peru that excludes the possibility of a heterogeneous nation.